Minat Mahasiswa Febira Unimuda terhadap Bisnis Digital - Khairunisa, Nur Afni; Jumroh, Lidya Aprilia; Sabaria; Alhazen, Tito (REMB : Research Economics Management and Business, 2025)
Unimuda's vision hopes that its graduates will enter the world of entrepreneurship. This vision really supports the Indonesian government in its efforts to create jobs and reduce unemployment. This research was conducted to obtain an overview of students' interest in the Faculty of Economics, Business and Humanities (Febira), Muhammadiyah Education University (Unimuda) Sorong to pursue digital business when they have completed their education. The sample used was Febira Unimuda Sorong students, 30% (90 respondents) of the total population. The sampling method was carried out using non-probability sampling with purposive sampling technique. Interest was measured by distributing questionnaires using a Likert scale (1. strongly disagree; 2. disagree, 3. neutral; 4. agree; 5. strongly agree). The data obtained was analyzed descriptively. The research results showed that of the 22 statement items, 6 of them were in the strongly agree category, the rest were in the agree category. It was concluded that Febira Unimuda Sorong students have a high interest in digital business.